A comparison on the execution of variables that determine successful mergers and acquisition activity in emerging markets : differences between emerging market multinational and developed market multinational corporations - Wocke, Albert (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2012.